Capecitabine, oxaliplatin and irinotecan in combination, with bevacizumab (COI-B regimen) as first-line treatment of patients with advanced colorectal cancer. An Italian Trials of Medical Oncology phase II study. Issue 4 (March 2015) - Di Bartolomeo, Maria; Ciarlo, Andrea; Bertolini, Alessandro; Barni, Sandro; Verusio, Claudio; Aitini, Enrico; Pietrantonio, Filippo; Iacovelli, Roberto; Dotti, Katia Fiorella; Maggi, Claudia; Perrone, Federica; Bajetta, Emilio
Abstract: Background: A dose-finding phase I/II trial that evaluated the maximum tolerated doses of a combination of three drugs with irinotecan, oxaliplatin and capecitabine (COI regimen) has been conducted in patients with metastatic colorectal cancer (mCRC). In this study the safety and activity of the combination of COI regimen plus bevacizumab (COI-B) were assessed. Methods: Patients judged to be unresectable for metastatic disease, were enrolled in a phase II, open-label study and treated with the combination of bevacizumab (5 mg/kg on day 1) and COI regimen (irinotecan 180 mg/mq on day 1, oxaliplatin 85 mg/mq on day 2, capecitabine 2000 mg d2–6; q14) as first-line treatment. Induction treatment was administered for a maximum of 8 cycles, followed by maintenance treatment with bevacizumab (7.5 mg/kg on d1, q21) until progression. Results: Fifty-one patients were enrolled in six Italian centres. The primary end-point of overall response rate was met, reaching the value of 62% in the per-protocol population and 57% in the intent-to-treat population, patients with stable disease were also taken into account, the clinical benefit rate was 94%. In the intention-to-treat population, median progression-free and overall survivals were 10.3 and 22 months, respectively. Toxicity was different from 5-fluorouracil-based triplet regimens, with 31% of severe diarrhoea, but a low incidence of grade 3/4 neutropenia (6%) and mucositis (4%). Conclusions: Our results show the feasibility and promising activity of the combination of capecitabine, oxaliplatin, irinotecan and bevacizumab.